Paraneoplastic Pemphigus Autoantibodies Against C-terminus of Desmoplakin Induced Acantholysis In Vitro and In Vivo - Wang, Xue; Wang, Rui; Bu, Dingfang; Wang, Leyi; Zhang, Yuexin; Chang, Yuan; Zhang, Chenyang; Chen, Xixue; Zhu, Xuejun; Liu, Zhi; Wang, Mingyue (Frontiers in Immunology, 2022)
Paraneoplastic pemphigus (PNP) is an autoimmune bullous disease associated with underlying neoplasms and characterized by antibodies against desmoglein 3 (Dsg 3) and plakins. Autoantibodies against desmoglein 3 in sera of patients with PNP have been proven to cause acantholysis in vivo in neonatal mice. As a member of the plakin family, autoantibodies against desmoplakin were detected frequently by immunoprecipitation in the sera of PNP. The recombinant C-terminus of desmoplakin was expressed and purified to adsorb the specific autoantibodies against the C-terminus of desmoplakin. In vitro dispase-dependent keratinocyte dissociation assay and in vivo IgG passive transfer into neonatal mice assay were performed, followed by the electronic microscopy examination and TUNEL assay. We found that anti-C terminus of desmoplakin autoantibodies caused blisters and acantholysis in mice skin at a dose-dependent manner. Moreover, dissociated fragments were observed after incubation with the purified IgG against desmoplakin, compared with normal human IgG (P-value =0.0207). The electronic microscopy examination showed the disconnection of keratin intermediate filaments from desmosomes. Lastly, apoptosis of keratinocytes in the TUNEL assay was all detected in the skins of neonatal mice after injection of the anti-C terminus of desmoplakin autoantibodies. Taken together, the study suggests that autoantibodies against the C-terminus of desmoplakin might be pathogenic in PNP.